Moral values found in the movie entitled chronicles of narnia: the prince of caspian adapted from clive staples lewis's novel - Adolf Bastian; Tahrun Tahrun; Hanny Yukamana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research aims to find out moral values in the Movie entitled Chronicles of Narnia: The Prince of Caspian Adapted from Clive Staples Lewis's Novel”. The Data of this research were obtained from words, phrase, sentences and utterance in the movie. To reveal the social-cultural background used in the movie the writer used documentation, interview, and movie review from another viewer. The moral values of the film are responsibility, honesty, love, and affection, strong belief, enthusiasm, Bravery, Goodhearted, loyalty, peace-loving, perseverance, sacrificing for others, sincerity and self-confidence. Byanalyzing moral values hopefully, it can build a good character for us as future teachers, and finally, we can give inspiration to the students. Learning English by watching movies is more enjoyable than learning through books.